ОСОБЕННОСТИ ПОСТРОЕНИЯ ЭЛЕКТРОМЕХАНИЧЕСКОЙ СИСТЕМЫ ОРИЕНТАЦИИ НАНОСПУТНИКА НА ОСНОВЕ БЕСКОНТАКТНОГО МАГНИТОЭЛЕКТРИЧЕСКОГО ДВИГАТЕЛЯ - Антонов, А.Е.; Акинин, К.П.; Киреев, В.Г. (Інститут електродинаміки НАН України, Київ, 2017)
Creation features of the magnetoelectric slotless motor for orientation of the nanosatellite systems are considered. The principles of the selection motor characteristics to minimize the weight and size, power consumption and stray field generated by the magnetic excitation of the engine system are considered. References 13, figures 2, table 1.